The social determinants of chronic disease management: perspectives of elderly patients with hypertension from low socio-economic background in Singapore - Sok Teng Tan; Rina Yu Chin Quek; Victoria Haldane; Joel Jun Kai Koh; Emeline Kai Lin Han; Suan Ee Ong; Fiona Leh Hoon Chuah; Helena Legido-Quigley (BMC, 2019)
Abstract Background In Singapore, the burden of hypertension disproportionately falls on the elderly population of low socio-economic status. Despite availability of effective treatment, studies have shown high prevalence of sub-optimal blood pressure control in this group. Poor hypertension management can be attributed to a number of personal factors including awareness, management skills and overall adherence to treatment. However, these factors are also closely linked to a broader range of community and policy factors. This paper explores the perceived social and physical environments of low socio-economic status and elderly patients with hypertension; and how the interplay of factors within these environments influences their ability to mobilise resources for hypertension management. Methods In-depth interviews were conducted in English, Chinese, Chinese dialects and Malay with 20 hypertensive patients of various ethnic backgrounds. Purposive sampling was adopted for recruitment of participants from a previous community health screening campaign. Interviews were translated into English and transcribed verbatim. We deductively analysed leveraging on the Social Model of Health to identify key themes, while inductive analysis was used simultaneously to allow sub-themes to emerge. Results and discussion Our finding shows that financing is an overarching topic embedded in most themes. Despite the availability of multiple safety nets, some patients were left out and lacked capital to navigate systems effectively, which resulted in delayed treatment or debt. The built environment played a significant role in enabling patients to access care easily and lead a more active lifestyle. A closer look is needed to enhance the capacity of patients with mobility challenges to enjoy equitable access. Furthermore, the establishment of community based elderly centres has enabled patients to engage in meaningful and healthy social activities. In contrast, participants' descriptions showed that their communication with healthcare professionals remained brief, and that personalised and meaningful interactions that are context and culturally specific are essential to advocate for patients' overall treatment adherence and lifestyle modification. Conclusion Elderly patients with hypertension from lower socio-economic background have various unmet needs in managing their hypertension and other comorbidities. These needs are closely related to broader societal factors such as socio-demographic characteristics, support systems, urban planning and public policies, and health systems factors. Policy decisions to address these needs require an integrated multi-sectoral approach grounded in the principles of health equity.